Population pharmacokinetics of brodalumab in patients with moderate to severe plaque psoriasis. Issue 1 (18th February 2019) - Timmermann, Stine; Hall, Anders
Abstract: Brodalumab is a fully human monoclonal antibody targeting the IL‐17 receptor A leading to an inhibition of the biological effect of IL‐17A, IL‐17F, IL‐17A/F heterodimer, IL‐17C and IL‐17E isoforms. It has shown to be efficacious in the treatment of moderate to severe plaque psoriasis (210 mg administered subcutaneously at weeks 0, 1 and 2 followed by 210 mg every 2 weeks [Q2W+1]). A population pharmacokinetic model based on psoriasis patients only from six clinical trials was developed to describe the pharmacokinetics and identify sources of variability. In patients with psoriasis, Brodalumab exhibits non‐linear pharmacokinetics due to target‐mediated drug disposition resulting in concentration‐dependent clearance. The pharmacokinetics was best described by a two‐compartment model with linear absorption and combined linear and Michaelis‐Menten elimination. The subcutaneous bioavailability of Brodalumab was 55%, absorption rate was 0.30 day −1, and body‐weight was found to affect the volume of distribution and clearance. For a reference patient with plaque psoriasis (body‐weight of 90 kg), the estimates were 0.16 L/d for linear serum clearance, 6.1 mg/d for the maximum non‐linear clearance rate, and 4.7 and 2.4 L for central and peripheral volume of distribution, respectively. For the approved dosing regimen, time to maximum concentration was 4 days and 90% of steady‐state was achieved after 10 weeks for a reference patient. Following last dose at steady‐state, 90% of the population of reference patients will reach serum concentrations below lower limit of quantification after 45 days.